Inappropriate sexual behaviour in secure psychiatric services: an evaluation of St Andrew’s Sexualised Behaviour Assessment (SASBA) - Price, Robyn (2020)
Incidents of unwanted sexual behaviour are common on mental health wards in England and Wales (Care Commission, 2018). This thesis aims to evaluate the utility of using St Andrew’s Sexualised Behaviour Assessment Scale (SASBA; Knight et al., 2008) for detecting sexual inappropriateness with mental health patients in forensic psychiatric settings. SASBA encourages continuous observation and recording of incidents of Inappropriate Sexual Behaviour (ISB), although it was initially designed for patients in neurorehabilitation settings. Chapter I introduces the challenges associated with measuring and defining sexual incidents. Chapter II provides a systematic review comparing SASBA and the few alternative behavioural tools. Chapters III and IV contain retrospective cohort studies that examine SASBA data in a mixed diagnosis mental health sample (n=137) and a psychosis subsample (n=72). Both samples included patients with and without sexual offence histories, providing the added opportunity to test for differences between sub-groups. The prevalence of ISB within groups was investigated and determined how monitoring should be targeted. Predictive factors for ISB behaviours in both studies were identified, and regression models were produced. The results suggested that SASBA is useful at detecting ISB in mental health samples, but is more relevant to sexually disinhibited psychotic patients than predatory sexual offenders. Chapter VI provides a summary of each section and a synthesis of the overall findings. Recommendations for future use and the limitations of retrospective data are also discussed.